2019
DOI: 10.1111/cas.14018
|View full text |Cite
|
Sign up to set email alerts
|

c‐Ski accelerates renal cancer progression by attenuating transforming growth factor β signaling

Abstract: Although transforming growth factor beta ( TGF ‐β) is known to be involved in the pathogenesis and progression of many cancers, its role in renal cancer has not been fully investigated. In the present study, we examined the role of TGF ‐β in clear cell renal carcinoma (cc RCC ) progression in vitro and in vivo. First, expression levels of TGF ‐β signaling pathway components were examined. Microarray and immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Taguchi and colleagues reported that in clear cell renal carcinoma (ccRCC) the signaling of TGFβ, but not that of BMP, works in a tumor-suppressive mode, by inducing apoptosis. Consistently, the transcriptional corepressor c-Ski, which is highly expressed in ccRCC, promotes tumor growth by counteracting the TGFβ-dependent SMAD arm (that requires SMAD2/3), but probably not that related to BMP (that requires SMAD1/5/8) [155]. However, in another study, BMP9 was shown to inhibit the proliferation of HCC cell lines via inducing, in a SMAD-independent mode, the expression of cell cycle inhibitor p21.…”
Section: Crosstalk Between Bmp and Tgfβ Pathway In Cancermentioning
confidence: 99%
“…Taguchi and colleagues reported that in clear cell renal carcinoma (ccRCC) the signaling of TGFβ, but not that of BMP, works in a tumor-suppressive mode, by inducing apoptosis. Consistently, the transcriptional corepressor c-Ski, which is highly expressed in ccRCC, promotes tumor growth by counteracting the TGFβ-dependent SMAD arm (that requires SMAD2/3), but probably not that related to BMP (that requires SMAD1/5/8) [155]. However, in another study, BMP9 was shown to inhibit the proliferation of HCC cell lines via inducing, in a SMAD-independent mode, the expression of cell cycle inhibitor p21.…”
Section: Crosstalk Between Bmp and Tgfβ Pathway In Cancermentioning
confidence: 99%
“…A549 cells were maintained in Dulbecco’s modified Eagle’s medium (#11965; Thermo Fisher Scientific, Waltham, MA) supplemented with 10% fetal bovine serum, 100 U/ml penicillin G, and 100 μg/ml streptomycin. To establish A549 cells stably expressing firefly luciferase and GFP under the CMV promoter, we used a lentiviral expression system (kindly provided by Prof. Hiroyuki Miyoshi, deceased, formerly Keio University, Tokyo, Japan) 46 . A549-Luc2-mCherry cells in the previous study were used as A549-mCherry cells 19 .…”
Section: Methodsmentioning
confidence: 99%
“…The lentiviral vector system (provided by H. Miyoshi, deceased, formerly Keio University) was used for speci c gene overexpression and knockdown as previously described. [29] For UQCRH overexpression, the complementary DNA encoding human UQCRH was inserted into the multiple cloning site of the empty vector pENTR201. Recombination between pENTR201 and the destination vector CSII-CMV-RfA was performed using Gateway cloning technology (Thermo Fisher Scienti c).…”
Section: Lentiviral Vector Construction and Productionmentioning
confidence: 99%
“…Mouse renal orthotopic tumor models were generated as previously described. [29] Brie y, BALB/c-nu/nu male mice (5weeks-old) were purchased from Sankyo Labo Service Corporation (Tokyo, Japan). ccRCC cells (1.0 × 10 5 ) expressing Luc2 and mCherry were inoculated into the subrenal capsule of mice.…”
Section: Mouse Renal Orthotopic Tumor Modelsmentioning
confidence: 99%